Awareness of the Study as Prevention of Early Termination of Studies - Ivana Nekvapilova; Jolana Fedorkova; Eva Jirouškova (Communications of International Proceedings, 2021)
Early termination of university studies is now considered nationally and internationally as a civil society, as one of several monitored indicators of the quality and performance of universities, which will affect the funding of the relevant educational institution. The paper discusses the basic parameters of the qualitative dimension of early termination of studies in the context of the media image of military university education –, in which the marketing of university education institutions plays a significant role. The unfulfilled expectations of students are a frequently mentioned factor in this context. The text has the character of a descriptive and comparative study. It focuses on finding out how selected military universities inform their future students about their educational environment on websites and social networks. It aims to answer the research question: Do all selected military universities provide the same information of the established factors of the 5-factor model of student decision-making when choosing a university? Using content analysis of available information sources and published outputs, it was found that selected universities do not provide the same information in terms of the 5-factor model of student decision-making when choosing a university. The subject of interest of the research study was marketing analysis of the media image of the only Czech military university – the University of Defense – and finding out whether the media messages are comparable with other foreign universities and meet students' expectations in the first semester of the academic year. The results of it are going applied in the next period for suggestions and recommendations of marketing activities of educational programs enhancing expectances of students and the competence of decision‑making.
Keywords: Early Termination of Studies; Tertiary Education; Expectations of Students; Media Presentation; Decision-Making Factors of Influence